Host-Specific Replication of BK Virus DNA in Mouse Cell Extracts Is Independently Controlled by DNA Polymerase α-Primase and Inhibitory Activities - Tikhanovich, Irina (American Society for Microbiology (ASM), 2010)
The activation of the human polyomavirus BK causes polyomavirus-associated nephropathy in immunocompromised humans. Studies of the virus have been restricted since the virus DNA replication is species specific. Cell-based and cell-free DNA replication systems, including the BK virus (BKV) monopolymerase DNA replication system using purified proteins, reproduce the species specificity (28). Therefore, the major host proteins comprising this assay, DNA polymerase α-primase (Pol-prim) and replication protein A (RPA), were intensively studied here. We demonstrate that Pol-prim plays a major role in the species specificity of BKV DNA replication. Both large subunits p180 and p68 of the enzyme complex have central functions in modulating the host specificity. Recently, an inhibitory activity of BKV DNA replication was described (C. Mahon, B. Liang, I. Tikhanovich, J. R. Abend, M. J. Imperiale, H. P. Nasheuer, and W. R. Folk, J. Virol. 83:5708-5717, 2009), but neither mouse Pol-prim nor mouse RPA diminishes cell-free BKV DNA replication. However, the inhibition of BKV DNA replication in mouse extracts depends on sequences flanking the core origin. In the presence of human Pol-prim, the inhibitory effect of mouse cell factors is abolished with plasmid DNAs containing the murine polyomavirus early promoter region, whereas the late enhancer region and the core origin are supplied from BKV. Thus, BKV replication is regulated by both Pol-prim, as a core origin species-specific factor, and inhibitory activities, as origin-flanking sequence-dependent factor(s).